2010
DOI: 10.31887/dcns.2010.12.3/mshenton
|View full text |Cite
|
Sign up to set email alerts
|

Structural neuroimaging in schizophrenia from methods to insights to treatments

Abstract: Historically, Kraepelin speculated that dementia praecox resulted from damage to the cerebral cortex, most notably the frontal and temporal cortices. It is only recently, however, that tools have been available to test this hypothesis. Now, more than a century later, we know that schizophrenia is a brain disorder. This knowledge comes from critical advances in imaging technology--including computerized axial tomography, magnetic resonance imaging, and diffusion imaging--all of which provide an unprecedented vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(19 citation statements)
references
References 65 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…Since the early observation of enlarged ventricles ( 130 ) in schizophrenia, there have been numerous computed tomography (CT) and structural magnetic resonance imaging (MRI) studies of the brain in this disorder. A number of reviews of this literature are available ( 131 , 132 ). Overall, these reviews have shown that patients with schizophrenia, when compared to healthy controls, show gray matter volume reductions in a number of brain areas.…”
Section: Genetic Cognitive and Neurobiological Studies Of Schizotypmentioning
confidence: 99%
“…Since the early observation of enlarged ventricles ( 130 ) in schizophrenia, there have been numerous computed tomography (CT) and structural magnetic resonance imaging (MRI) studies of the brain in this disorder. A number of reviews of this literature are available ( 131 , 132 ). Overall, these reviews have shown that patients with schizophrenia, when compared to healthy controls, show gray matter volume reductions in a number of brain areas.…”
Section: Genetic Cognitive and Neurobiological Studies Of Schizotypmentioning
confidence: 99%
“…The frontal lobe is one of the major regions to receive attention in the search for the neural substrates of schizophrenia. Several MRI studies have reported volume reductions in schizophrenia (see review by Shenton et al [ 11 ••]). Involvement of the frontal lobe has been related to negative symptoms and cognitive impairments in schizophrenia, including deficits in executive and problem-solving functions and working memory [ 12 , 13 ].…”
Section: Structural Mri Studies Of Schizotypal Personality Disordermentioning
confidence: 99%
“…In the present study, regional cortical volumes generated using automated segmentation and parcellation by FreeSurfer [ 32 ] did not show significant volumetric differences between schizophrenia and healthy control subjects. Previous ROI-based analyses using manual, semi-automated and fully automated regional parcellation schemes have reported morphometric abnormalities in schizophrenia subjects [ 3 , 10 , 12 ]. Many of these studies are limited by small sample sizes ( N = 12-22) [ 33 , 34 ], variable duration of illness and clinical heterogeneity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain morphometric abnormalities have been extensively reported in schizophrenia for more than three decades. Following the initial report of brain volume reductions in schizophrenia by Johnstone et al [ 1 ] in their computerized tomographic (CT) study, there have been an ever-increasing number of reports of brain morphometric abnormalities in schizophrenia using more powerful imaging modalities [ 2 , 3 ]. These studies have used various quantitative measurements such as ventricular: brain ratio (VBR), whole brain volume, lobar volumes, volumes generated by region-of-interest (ROI)-based parcellation of cortical and subcortical structures using manual or semi-automated methods, as well as whole-brain voxel-based or surface-based analyses [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation